2021
DOI: 10.1186/s12957-021-02355-7
|View full text |Cite
|
Sign up to set email alerts
|

Is three-dimensional–printed custom-made ultra-short stem with a porous structure an acceptable reconstructive alternative in peri-knee metaphysis for the tumorous bone defect?

Abstract: Background Long-lasting reconstruction after extensive resection involving peri-knee metaphysis is a challenging problem in orthopedic oncology. Various reconstruction methods have been proposed, but they are characterized by a high complication rate. The purposes of this study were to (1) assess osseointegration at the bone implant interface and correlated incidence of aseptic loosening; (2) identify complications including infection, endoprosthesis fracture, periprosthetic fracture, leg lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Efforts to improve metaphysis fixation can be summarized into two categories. One is auxiliary fixation structure to enhance reconstruction, the other is a surface modification to achieve osseointegration ( Bini et al, 2000 ; Dieckmann et al, 2014 ; Stevenson et al, 2017 ; Bernthal et al, 2019 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to improve metaphysis fixation can be summarized into two categories. One is auxiliary fixation structure to enhance reconstruction, the other is a surface modification to achieve osseointegration ( Bini et al, 2000 ; Dieckmann et al, 2014 ; Stevenson et al, 2017 ; Bernthal et al, 2019 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to improve metaphysis fixation can be summarized into two categories. One is auxiliary fixation structure to enhance reconstruction, the other is a surface modification to achieve osseointegration (Bini et al, 2000;Dieckmann et al, 2014;Stevenson et al, 2017;Bernthal et al, 2019;Wang et al, 2021). Stevenson et al (2017) reported that HA (hydroxyapatite) coated extra-cortical plates increased the survivorship of shortcemented-stemmed endoprostheses.…”
Section: Efforts To Improve Metaphysis Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…The femur is a common site for primary bone tumours, but a diaphyseal location is less common than at the extremities [ 1 ]. Several techniques have been described for reconstruction after extensive diaphyseal femoral resection (> 10 cm) [ 2 ]: biological reconstructions: vascularised autograft [ 3 ], Masquelet’s induced membrane [ 4 ], allograft [ 5 ], combined graft [ 6 ], or even distraction osteogenesis or transport techniques [ 7 ], and finally prosthetic reconstructions using segmental prostheses, or custom reconstructions [ 8 11 ]. Some other innovative biologic techniques are also described but with a short follow-up on a small cohort [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, long-term survival is questionable with these implants. Although they allow early weight-bearing, the rate of complications is high (up to 60%), consisting primarily of infections, fractures, and loosening [ 11 , 13 ]. Several authors also report the use of devitalised tumour-bearing bone with interesting results, but with tumour histological analysis potential issues [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%